Leaf sugar metabolomic profiling reveals differences between Coffea arabica cultivars in two locations of Cerrado Mineiro (Brazil) - Carréra, Jéfyne Campos (2023)
29th Conference of Association for the Science and Information on Coffee, 11 Sept. - 14 Sept. 2023 Hanoi, Vietnam